Experiencing tensions of nepantla with inner-departmental change groups - Hagman, Jess Ellis; Voigt, Matthew; Bennett, Amy Been; Nicole, Fantasi; Bolick, Margaret Ann; Pai, Leilani; Kress, Nancy; Quaisley, Kelsey; Tremaine, Rachel; Funk, Rachel; Wonch Hill, Patricia; Smith, Wendy M. (Frontiers in Education, 2024)
This study explores the experiences of three Networked Improvement Communities (NICs) within mathematics departments as they work to critically transform their introductory mathematics programs. Drawing on Gutiérrez's (2002; 2013) framework of dominant and critical axes of equity, we identify three key tensions experienced by the NICs: identity neutrality versus identity centrality, power over versus power with, and students as novices versus students as experts. These tensions are framed as productive enactments of working to change systems from within, highlighting the challenges and opportunities inherent in navigating the liminal space of nepantla. We argue that engaging with these tensions is crucial for fostering critical transformations and offer recommendations for leveraging the roles of identity, power, and student partnership to promote more equitable and inclusive mathematics education environments.Author Contributions JEH, MV, and ABB were involved in writing the original draft, reviewing and editing, conceptualization, investigation, formal analysis, and supervision. FN was involved with writing the original draft, reviewing and editing, and visualization. MAB was involved with writing the original draft, reviewing and editing, conceptualization, investigation, formal analysis, and visualization. LB was involved with writing the original draft, reviewing and editing, conceptualization, and formal analysis. NK was involved in writing the original draft, reviewing and editing, and conceptualization. KQ was involved in reviewing and editing, conceptualization, investigation, and formal analysis. RF was involved in conceptualization, investigation, and project administration. RT and PWH were involved in conceptualization and investigation. WMS was involved in reviewing and editing, conceptualization, investigation, and project administration.